William Hone - parodist and radical - Abreu, Maria Georgina Ribeiro Pinto de (2004)
William Hone produced violent anti-government parodies in partnership with the leading caricaturist of the day, George Cruikshank (1792-1878). According to Marcus Wood,1 Hone and Cruikshank’s was the most widely circulated and influential satire printed during the period 1815-22, the period Thompson designated as ‘the heroic age of popular radicalism’. This essay examines Hone’s activity as author and publisher of political parodies between 1815 and 1817.